Social Media and the Olympics: A Chance for Improving Gender Equality - Grabmüllerová, Aneta (Frontiers in Sports and Active Living, 2022)
The purpose of this paper is to explore whether social media coverage by the National Olympic Committees (NOC) during the 2020 Tokyo Olympic Games strengthens or weakens the International Olympic Committee’s (IOC) gender equality ambitions. As the media play an important role in creating the impressions that people cherish during and after the Olympics, the IOC has since the 1990s increased its responsibility for fair media portrayal of athletes and competitions by revising its own media production. In the past decade, this most notably concerns social media. Not only has it become an inseparable part of global sports consumption, but it is also seen as a tool for changing the biased and stereotypical portrayal of female athletes in news media, even though male and female athletes have become nearly equal in numbers of participants. Studies of media production and equality-informed decisions are, however, rare in sport. Drawing upon a quantitative analysis of social media accounts of three National Olympic Committees (NOC) (Norway, Czech Republic and Switzerland) and qualitative in-depth interviews with key informants – NOCs’ and European Olympic Committee’s (EOC) social media personnel – this study therefore explored the decisions and processes that influenced gender portrayal during the 2020 Tokyo Olympics. Findings of the study showed that media personnel have a significant influence on gender portrayal in their respective communication channels. In contrast to news media, they were aware of the frames they apply, and they applied them in alignment with the Olympic values. Consequently, they set a fairer agenda for both male and female athletes and strengthened the gender equality mission of the IOC.